Dental complications of radiotherapy: clinical picture, diagnostics, treatment. A review of the literature - Michalak, Piotr; Krzywda, Anna; Hajto-Bryk, Justyna; Zarzecka, Joanna (Journal of Stomatology, 2019)
The use of radiotherapy in the treatment of head and neck cancers leads to complications in tooth tissues and caries progression caused by changes in the amount and composition of saliva and bacterial microflora. The aim of this article was to review and summarise knowledge about dental complications of radiotherapy among oncological patients with head and neck cancer (HNC). A search of the literature was performed using the keywords radiotherapy, tumours of the head and neck, and radiation caries in the PubMed database and epidemiological data from the Polish National Cancer Register. The selection of the most comprehensive papers published until October 2018 was analysed. According to the analysis of the reviewed literature dentists did not have clear recommendations for treatment and follow-up of patients after radiotherapy. A complex approach may prevent irreversible changes in the oral cavity, e.g. teeth damage. Radiation-induced caries have multifactorial aetiology; thus oncological patients require constant, careful and comprehensive dental care before, during and after irradiation. Various conflicting results of many studies were obtained. Studies were conducted in different conditions (in vivo, in vitro) that led to creation of different protocols of proceedings. The best practice is to follow the guidelines to ensure the best patient care and standardisation of treatment. There is a need to reach an international consensus.